-4(0.3x+0.6)-1.3=-0.1

Simple and best practice solution for -4(0.3x+0.6)-1.3=-0.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(0.3x+0.6)-1.3=-0.1 equation:


Simplifying
-4(0.3x + 0.6) + -1.3 = -0.1

Reorder the terms:
-4(0.6 + 0.3x) + -1.3 = -0.1
(0.6 * -4 + 0.3x * -4) + -1.3 = -0.1
(-2.4 + -1.2x) + -1.3 = -0.1

Reorder the terms:
-2.4 + -1.3 + -1.2x = -0.1

Combine like terms: -2.4 + -1.3 = -3.7
-3.7 + -1.2x = -0.1

Solving
-3.7 + -1.2x = -0.1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3.7' to each side of the equation.
-3.7 + 3.7 + -1.2x = -0.1 + 3.7

Combine like terms: -3.7 + 3.7 = 0.0
0.0 + -1.2x = -0.1 + 3.7
-1.2x = -0.1 + 3.7

Combine like terms: -0.1 + 3.7 = 3.6
-1.2x = 3.6

Divide each side by '-1.2'.
x = -3

Simplifying
x = -3

See similar equations:

| 28-1+10=x-1 | | ln(40)-2ln(5)=0 | | 9z+29x=8x-13 | | 34-3x=16 | | -19+x-2=11-19+9 | | 4x+7=20(3-2x)+7 | | 17-8+x=8+7-3 | | -23+(-45)= | | 0.2x+9.7=8.4 | | 3(x+5)=6x+8 | | 8(x-8)=24-3x | | 20+5x+4x-11=180 | | 9(2)+3y=4y-9(4) | | (1/2)(6x-8)=(7/5)(x-5)-(1/5) | | 1x+25=-3 | | -6=x+100 | | 2x+x=359 | | 60=-w+176 | | 36-x=267 | | 158=239-u | | 1(15x)+25=-3 | | 245=-u+123 | | 7/2=3/2n-7/2n | | 5-4x=4x-5-4x-2 | | 8+8x=14+8x | | 14-(3a+2)= | | 1.4=log(x) | | 7z+5-2z=47-2z | | 7x-2(2x-1)=17 | | 25-(25x)=22 | | 25-(25x)=10 | | 4(w+3)=8(w-1) |

Equations solver categories